Reductive pyrolysis of Miocene-aged lignite humic acids, Bulgaria. (1st February 2016) - Stefanova, Maya; Gonsalvesh, Lenia; Marinov, Stefan; Czech, Jan; Carleer, Robert; Yperman, Jan
Abstract: Atmosphere Pressure–Temperature Programmed Reduction (AP–TPR) technique coupled "off-line" with thermal desorption gas chromatography–mass spectrometry (TD-GC/MS) can be effectively used to specify qualitatively/quantitatively organic functionalities in humic substances. The AP–TPR technique has been initially developed and successfully applied for sulphur speciation in coals and in their biodesulphurized products. The aim of the present study is to analyze volatiles in flue gases of a reductive pyrolysis of Miocene-aged lignite humic acids by AP–TPR "off-line" TD-GC/MS and to assign identified components to the structural compositions of the samples studied. Humic acids from two coal-bearing provinces in Bulgaria, i.e. Thrace and Sofia, have been considered. The following compounds were tracked and quantified in the flue gases released during the AP–TPR experiments: aliphatics, i.e. n C6 – n C14, mono unsaturated/saturated pairs, alkylated benzenes, styrenes, naphthalenes, biphenyls, fluorene, acenaphthylene; oxygen containing compounds, i.e. phenols, methoxy phenols, furans, benzofurans; sulphur containing compounds, i.e. sulphides, thiophenes, benzothiophenes; nitrogen containing compounds, i.e. pyrroles, indoles, quinolines, benzonitriles, etc. Total content of organics in pyrolysates amounts to 55.9 mg/g Corg for Thrace humic acids (Maritza-East deposit) and 55.0 mg/g Corg for Sofia humic acids (Stanjanci deposit). Alkyl benzenes (C6 –C10 ) highly dominate in the programs up to half of the recorded components (46–58 rel.%). The low sample maturity is reflected in high abundance of phenols, C6 –C8 (20 rel.%), methoxy phenols (2.7 rel.%) and degradation products from carbohydrates, i.e. furaldehydes, 2-cyclopenten-1-ones, etc. Plots of four group composites, i.e. aliphatics, aromatics, O-, S- and N-containing compounds, in "spider web" diagram seem promising for bulk interpretation of pyrolysates data. According to the reductive pyrolysis data, structural units of Miocene-aged humic acids are composed by 1–2 aromatic rings, condensed or coupled, including heteroatoms arranged in linear and cyclic forms.